Detection of Candida auris Antifungal Drug Resistance Markers Directly from Clinical Skin Swabs - Kordalewska, Milena (Antimicrob Agents Chemother, 2019)
Accurate and rapid assessment of Candida auris antifungal drug resistance is crucial for effective infection prevention and control actions, as well as for patient management. Here, performance of a molecular diagnostic platform, enabling rapid identification of FKS1 and ERG11 mutations conferring echinocandin and azole resistance, respectively, was evaluated on a panel of clinical skin swabs. Gene sequencing and antifungal susceptibility testing were used as the gold standard. All swabs were correctly categorized as harboring wild-type or mutant C. auris.